A comparison of epiphytic diatom communities on Plocamium cartilagineum (Plocamiales, Florideophyceae) from two Antarctic areas - Majewska R.; Kuklinski, P; Balazy P; Yokoya N; S; Paternostro A; M; DE STEFANO, Mario (Polar Biology, 2015)
Our understanding of diatoms, one of the most important Antarctic primary producers, is based mostly on investigations of plankton, sea-ice, and sediment samples. Herein, we contribute to the limited research devoted to benthic Antarctic diatoms by presenting a study on epiphytic diatom communities sampled in two remote Antarctic regions: Admiralty Bay (maritime Antarctica, Antarctic Peninsula) and Terra Nova Bay (Ross Sea). Recent studies have demonstrated that the most critical factor for the local epiphytic diatom communities was the nature of the substrate. In order to eliminate this factor so we could evaluate other potential controls, we sampled epiphytic diatoms from only one substrate that is common to both regions: the macroalgae Plocamium cartilagineum (L.) Dixon. Thalli of P. cartilagineum and their associated microalgal community was collected in January 2011 (Admiralty Bay) and 2012 (Terra Nova Bay) from a water depth of 5–25 m. Dehydrated macroalgal pieces were placed on stubs and sputter-coated, which allowed observation of diatoms attached to the substrate in their original position using scanning electron microscopy. A total of 72 taxa were observed, of which 31 taxa were common to both regions. Cell abundance and diatom growth form dominance were significantly different in Admiralty Bay and Terra Nova Bay samples. Total diatom abundance was higher in Admiralty Bay samples, dominated by adnate diatoms (Cocconeis spp.), but the number of taxa found as well as the values of ecological indices were higher for samples from the Ross Sea, where motile forms were dominant (Navicula spp.). Our results suggest that Antarctic shallow-water benthic habitats may present a high degree of microniche heterogeneity and highlight the need of fine-scale analyses in microbial studies. We also suggest grazers as a factor that contributes greatly to the observed differences. Our understanding of diatoms, one of the most important Antarctic primary producers, is based mostly on investigations of plankton, sea-ice, ...